Analisis Penurunan Tingkat Kecacatan Dengan Menggunakan Metode DMAIC Di PT.X - Andre Santoso; Prayonne Adi (Jurnal Titra, 2023)
PT.X is a company that produces iodised salt with 2 types of salt, namely consumption salt and industrial salt. One of the things that must be maintained by the company is the problem of quality. The right quality can give a good reputation for the company. The purpose of this study is to analyze the existence of defects with the aim of reducing rework so that packaging does not occur at the end and the process is repeated. The method used in this research is DMAIC. The defect problems that will be discussed in this study are the appearance of spots on the salt, torn packaging, inadequate packaging, coarse salt, and short length packages. For the analyze phase, the 5 whys tools are used. Then, at the measure stage, six sigma tools, namely DPMO, are used to find out the possible defects that occur every 1 million times of production. The calculation is then followed by a sigma value to determine the process capability of the company. This tool is one of the six sigma tools used for statistical data analysis.